A novel mutation in the thiamine responsive megaloblastic anaemia gene SLC19A2 in a patient with deficiency of respiratory chain complex I. Issue 9 (1st September 2000) - Scharfe, Curt; Hauschild, Michael; Klopstock, Thomas; Janssen, Antoon J M; Heidemann, Peter H; Meitinger, Thomas; Jaksch, Michaela
Abstract : The thiamine transporter gene SLC19A2 was recently found to be mutated in thiamine responsive megaloblastic anaemia with diabetes and deafness (TRMA, Rogers syndrome), an early onset autosomal recessive disorder. We now report a novel G1074A transition mutation in exon 4 of the SLC19A2 gene, predicting a Trp358 to ter change, in a girl with consanguineous parents. In addition to the typical triad of Rogers syndrome, the girl presented with short stature, hepatosplenomegaly, retinal degeneration, and a brain MRI lesion. Both muscle and skin biopsies were obtained before high dose thiamine supplementation. While no mitochondrial abnormalities were seen on morphological examination of muscle, biochemical analysis showed a severe deficiency of pyruvate dehydrogenase and complex I of the respiratory chain. In the patient's fibroblasts, the supplementation with high doses of thiamine resulted in restoration of complex I activity. In conclusion, we provide evidence that thiamine deficiency affects complex I activity. The clinical features of TRMA, resembling in part those found in typical mitochondrial disorders with complex I deficiency, may be caused by a secondary defect in mitochondrial energy production.